Calibration bias of experimentally determined chlorine isotope enrichment factors: the need for a two‐point calibration in compound‐specific chlorine isotope analysis. (28th November 2016) - Ebert, Karin A.; Laskov, Christine; Elsner, Martin; Haderlein, Stefan B.
Abstract : Rationale: The recent development of compound‐specific online chlorine isotope analysis ( 37 Cl‐CSIA) methods has fostered dual chlorine–carbon isotope studies to gain better insights into sources and environmental transformation reactions of chlorinated ethenes. One‐point and two‐point calibration schemes are currently used to convert raw data to the international δ 37 ClSMOC scale, but a critical evaluation of best practices to arrive at reliable δ 37 ClSMOC signatures and enrichment factors was missing and is presented here. Methods: Aqueous solutions of neat perchloroethylene and trichloroethylene (TCE) and aqueous samples from a TCE biodegradation experiment with pure cultures of Desulfitobacterium hafniense Y51 were analysed for their chlorine isotope ratios using GC/qMS and GC/IRMS. The δ 37 ClSMOC values were obtained using one‐point and two‐point calibration schemes. Chlorine isotope enrichment factors, ε Cl, were calculated using both approaches and the corresponding bias of δ 37 ClSMOC values introduced by the different types of calibration was determined. Results: Different calibration methods resulted in significant differences (up to 30%) in both δ 37 Cl signatures and ε Cl values. Conclusions: Our results demonstrate that a two‐point calibration together with comprehensive information on reference materials is indispensable and should become standard practice for reliable 37 Cl‐CSIA of organic compounds. Copyright © 2016 John Wiley & Sons, Ltd.